Synthesis and crystal structure of multicomponent ceramics YBa2CuR2O6 and YBa4R3O9 (R = Cu, Mg, Zn, Ni, Co) - Semen’ko, M.P.; Belyavina, N.N.; Nakonechna, О.І.; Kuryliuk, A.M. (Reports of the National Academy of Sciences of Ukraine, 2022)
High entropy oxides YBa2CuR2O6 and YBa4R3O9 have been synthesized by the method of solid-phase synthesis from a charge, which contains such common counterparts as BaCO3, Y2O3 and CuO along with the equimolar mixture of oxides CuO, MgO, ZnO, NiO and CoO (conditionally labelled as RO). Phase composition and crystal structure refinement of the products synthesized has been provided by X-ray powder diffraction. It has been shown that a well known rhombic compound r-YBa2Cu3O7 with a = 0. 3834(2) nm, b = 0. 3888(2) nm, c = 0. 3888(2) nm is formed under the conditions of solid-phase synthesis carried out without the use of a multicomponent mixture of oxides. While the use of RO oxide in the charge leads to the formation of phases related to the known structural types of t-YBa2Cu3O6 and YBa4Cu3O9, namely, the tetragonal phase YBa2CuR2O6 with a = 0. 3877(2) nm, c = 1. 1632(7) nm and the cubic phase of YBa4R3O9 with a = 0. 8228(2) nm. Analysis of the atom’s location in the regular systems of points of structures of multicomponent phases YBa2CuR2O6 and YBa4R3O9 indicates that the conditional “high-entropy” cationic component R = CuMgZnNiCo occupies only the position with an octahedral environment of oxygen atoms in these structures. Therefore, if there are positions with an octahedral RO6 environment in the designed multicomponent oxide compounds, the use of “high-entropy” component of the charge R = Cu, Mg, Zn, Ni, Co to create new single-phase high entriopy oxide materials with oxygen is very effective.